2014
DOI: 10.5424/sjar/2014123-5186
|View full text |Cite
|
Sign up to set email alerts
|

Development of models to predict product deposition from coverage obtained on artificial collectors and their practical application

Abstract: Models to relate the observed coverage on artificial collectors used in field tests (water-sensitive paper, WSP) and in laboratory bioassays of citrus pests (pieces of polyvinyl chloride sheets, PVC) with product deposition are described. Different solutions of plant protection products commonly used for pest control in citrus were sprayed in a Potter Tower on PVC and WSP under the same controlled conditions. These experiments led to the formulation of different basic models to relate coverage and deposition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Stains on WSP are larger than the area covered by the initial droplet due to the solution spreading . As WSP absorbs and expands the aqueous portion of a pesticide spray, it has been suggested that the measurement of WSP stains can overestimate the liquid deposition, as the stains created appear larger than the initial droplet. However, through using a spread factor, this error can be accounted for.…”
Section: Methodsmentioning
confidence: 99%
“…Stains on WSP are larger than the area covered by the initial droplet due to the solution spreading . As WSP absorbs and expands the aqueous portion of a pesticide spray, it has been suggested that the measurement of WSP stains can overestimate the liquid deposition, as the stains created appear larger than the initial droplet. However, through using a spread factor, this error can be accounted for.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of spray coverage was done prior to the application of experimental treatments; therefore water was sprayed during these experiments. A previous study showed that similar coverage on WSP is obtained with both Reldan® and water (Garcerá et al, 2014b). Once the trees were sprayed and the WSP had dried, the pieces were collected and stored in dry conditions.…”
Section: Application Timing Decisionmentioning
confidence: 97%
“…Some advanced technologies, such as geographic information systems, differential global positioning, electronic-guidance, on-site meteorological monitoring, and remote sensing, can optimize herbicide application for maximum efficacy and environmental protection [3]. Cruz Garcera opened a possibility to estimate the deposition of a plant protection product in field applications from coverage values measured on WSP [4].…”
Section: Introductionmentioning
confidence: 99%